The Development of Music Teaching Strategies for Promoting Music Learning Competency for Elementary School Students Under the Core Literacy of Music Academic Subjects - He, Yudong; Suttachitt, Narutt (Journal of Ecohumanism, 2024)
This study examines the current problem and effect of music teaching, develops music teaching strategies for promoting music learning competency, and studies the efficiency of these strategies in elementary school students. It employs a mixed-method research approach, collecting data through questionnaires, in-depth interviews, and observation from 160 music teachers and department managers. Data were analyzed using descriptive statistics, inferential statistics, one-way ANOVA, and Multiple Regression.The findings reveal that current problems of music teaching are Aesthetic perceptions, Artistic expression, and cultural understanding affect the innovation of music-teaching strategies of elementary students, and they are currently in low level. Innovative music teaching strategies compose of Incorporating Chinese Cultural Elements, using Interactive and Engaging Methods, differentiating Instruction by Skill Levels, focusing on Basic Music Competencies, encouraging Creativity and Expression, Professional Development for Teachers, and Parental and Community Involvement. The overall efficiency and satisfaction of music teaching strategies for elementary students was at the highest level. The posttest correct answers increased by 34.0%, which shows that the innovative teaching strategy for music learning is effective.